The influence of working capital on corporate performance: evidence from Latin America - Bozzeda, Riccardo (2017)
This paper provides evidence of the effect of Working Capital Management (WCM) on the performance of Latin America companies. The study also investigates whether the effect of WCM on performance differs between ‘small’ and ‘big’ firms. The paper employs Panel data regression analysis on a sample of 117 non-financial firms over an eleven-year period (2005- 2015). The results show that WCM has a convex relationship with performance. However, the results suggest that WCM is relatively more important for the performance of ‘big’ companies than ‘small’ companies. Overall, the study proves that WCM components do affect the performance of Latin America firms.